Inquiry-based E-LKPD in effort to improve the fourth grade students’ learning outcome - Samsi Nur Hidayati; Sunyono Sunyono; Lilik Sabdaningtyas (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This study aims to determine 1) the feasibility of inquiry-based e-LKPD, 2) the importance of e-LKPD in the process of learning mathematics in elementary schools, 3) the improvement of students' mathematics learning outcome. The syntax of inquiry-based e-LKPD is student orientation to problems, organizing students to learn, guiding the investigation of individual and group participants, developing and presenting work results, analyzing and evaluating problem-solving processes. The data were collected through interviews, questionnaires, and tests. The results showed that the low thematic learning outcomes of students was due to the fact that educators had not fully used teaching materials and models that could improve learning outcomes, so it was hoped that the inquiry-based e-LKPD could improve the fourth grade students’ thematic learning. It is clear that inquiry is one of the learning strategies that can be applied as a solution in improving student learning outcomes, in accordance with the characteristics of the students. Therefore, it can be concluded that the inquiry-based e-LKPD to improve student learning outcomes in elementary schools needs to be developed.